2022
DOI: 10.1002/adfm.202200011
|View full text |Cite
|
Sign up to set email alerts
|

Bone Microenvironment‐Mimetic Scaffolds with Hierarchical Microstructure for Enhanced Vascularization and Bone Regeneration

Abstract: Microchannel networks within engineered 3D scaffold can allow nutrient exchange and rapid blood vessels formation. However, fabrication of a bone microenvironment‐mimicking scaffold with hierarchical micro/nanofibrous and microchannel structures is still a challenge. Herein, inspired by structural and functional cues of bone remodeling, a microchannel networks‐enriched nanofibrous scaffold by using 3D printing and thermally induced phase separation techniques, which can facilitate cells migration and nutrients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
111
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(129 citation statements)
references
References 58 publications
1
111
0
Order By: Relevance
“…[ 13 ] Therefore, RT‐qPCR and western blot were carried out to evaluate the effect of SGL‐NP@Eth scaffold on the osteogenic activities of BMSCs grown on the scaffold, and the effect of osteoclastic activity of BMMCs was also assessed. [ 51 ] Figure A–D shows the expression levels of osteogenic genes of BMSCs, including runt‐related transcription factor 2 (RUNX2), Osterix, OPN, and collagen type I (Col1a). The expressions levels of RUNX2 and Osterix were significantly increased in SGL‐NP@Eth (ISO (+)) and SGL (ISO (+)) groups compared to SG (ISO (+)) group at day 7.…”
Section: Resultsmentioning
confidence: 99%
“…[ 13 ] Therefore, RT‐qPCR and western blot were carried out to evaluate the effect of SGL‐NP@Eth scaffold on the osteogenic activities of BMSCs grown on the scaffold, and the effect of osteoclastic activity of BMMCs was also assessed. [ 51 ] Figure A–D shows the expression levels of osteogenic genes of BMSCs, including runt‐related transcription factor 2 (RUNX2), Osterix, OPN, and collagen type I (Col1a). The expressions levels of RUNX2 and Osterix were significantly increased in SGL‐NP@Eth (ISO (+)) and SGL (ISO (+)) groups compared to SG (ISO (+)) group at day 7.…”
Section: Resultsmentioning
confidence: 99%
“…59 Microchannel scaffolds loaded with osteogenic peptide-1 bone forming peptide can significantly stimulate vascular EC migration, tube formation, and angiogenesis-related gene/protein expression to promote angiogenesis (Figure 3A). 60 Cryodeposition modeling low-temperature deposition modeling-printed sponges containing MSCs significantly promoted vascularized bone regeneration (Figure 3B). 61 The porous structure of the microspheres facilitates cell adhesion and provides a large surface area for cell proliferation.…”
Section: Construct a Mechanical Structure That Promotes The Vasculari...mentioning
confidence: 95%
“…(A) Hollow polycaprolactone (PCL) scaffold with interconnected microchannel networks could promote angiogenesis and osteogenesis. Copyright permission from Ha et al 60 (B) Schematic illustration of highly interconnected porous structure to achieve vascularized bone regeneration. Copyright permission from Lian et al 61 (C) Microspheres and cell morphology observed under scanning electron microscope (SEM) for human umbilical vein endothelial cells (HUVECs) cultured on microspheres for 7 days.…”
Section: Application Of Biomaterials In Tissue Engineering Vasculariz...mentioning
confidence: 99%
“…[62,63] As an alternative, many scaffolds or bonesubstitute biomaterials have been developed to reconstruct the defects and regenerate bone tissues. [63,64] One of the key requirements of bone tissue engineering is the design and development of tissue engineering scaffolds that recapitulate important characteristics of bone to mimic native bone tissue function and therefore regenerate the damaged tissues. [65][66][67] In addition to the antibacterial and biocompatibility of Ti 3 C 2 MXene, they have Ca 2+ binding sites which promote osteogenesis.…”
Section: Bone Regenerationmentioning
confidence: 99%